The metronome marks for Beethoven’s Ninth Symphony in context - Noorduin, M (Oxford University Press, 2021)
In recent years, Beethoven’s metronome marks for his Ninth Symphony have experienced a renewed relevance, with several ensembles incorporating the indicated speeds in their performances. Nevertheless, previous research has shown that some of the marks have been incorrectly transmitted, and there is the suspicion that further mistakes are still undiscovered. Focusing particularly on the second and fourth movements, this article discusses the historical sources and scholarly contexts for these markings, within a historical framework that draws on Beethoven’s general tempo principles, as well as observations from contemporaries. The article suggests that the trio of the second movement has three speeds that can be justified historically, although the most popular option, minim = 160, arguably has the least supporting evidence. The discussion also draws attention to another metronome mark for the final section of the symphony that has been often overlooked. Finally, it argues that one of the most often cited examples of an erroneously transmitted metronome mark, the dotted minim = 96 for the Schreckensfanfare found in the later sources, is consistent with Beethoven’s wider practice, and should provide an incentive for performers to experiment with historically informed tempi in this familiar repertory.